PERANAN HAKIM DALAM MELAKUKAN PENEGAKAN HUKUM PROGRESIF - Elmayanti, Elmayanti (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
The role of judge to commit progressive law enforcement is to prevent crisis of law and to erect supremacy of law in Indonesian. The judge can’t only to follow procedural justice but also must to purpose substantive justice. Progressive law paradigm is law can suffice need nation and also to feel suffering this nation. So the law to serve public interest not on the contrary, law can’t exist in atmosphere or vacuum room, but law exist in public. Law according to value real and justice